(untitled) (Alternautas, 2024)
Fifty years after the coup d`état in Chile, cities such as Amsterdam, Frankfurt, Leeds, Milan, Belgrade, Los Angeles, and Chicago, still display traces of Chilean exile on the walls of cultural centres, universities, theatres and other buildings. These are the remains of hundreds of murals, painted by brigades created by Chileans in exile to encourage their host countries to show solidarity with their resistance to the Pinochet dictatorship. The complex experience of Chilean exile and its long-lasting and intergenerational repercussions have only slowly been integrated into research and memory practices. This article examines three case studies of Chilean murals in exile as atypical forms of testimonial sources, with the aim of gaining insights into the multi-layered network of actors behind them, in particular into the testimonies of Chilean exiles and actors of international solidarity. It also explores the memorial dimensions of postephemeral murals and how these can function as carriers of a collective, transnational memory of Chilean exile.